Donner naissance: doulas, sages-femmes & justice reproductive - Apfel, Alana; Ross, Loretta J.; Law, Victoria; Federici, Silvia; Pruvost, Geneviève; Tincelin, Adel (Sorcières, 2024)
Donner naissance . Doulas, sages-femmes & justice reproductive . Alana Apfel nous propose un recueil vivant de treize récits écrits par des doutas, des sages-femmes et des activistes féministes aux États-Unis qui racontent la naissance autrement. Au modèle de la toute-puissance médicale qui saurait mieux que les femmes elles-mêmes ce qu'est un « bon » accouchement est opposé ici un tout autre professionnalisme, à la fois discret et attentif, qui permet de faire une juste place à des femmes indignement traitées. Militer pour la « justice reproductive », c'est créer des « communs » de la naissance, selon la formule de Silvia Federici dans son introduction.. La postface de Geneviève Pruvost nous rappelle que l'obstétrique française est la plus médicalisée d'Europe. À l'heure où, en France, les sages-femmes à domicile font l'objet d'une tentative d'éradication professionnelle, Donner naissance nous propose une nouvelle manière de penser les trajectoires reproductives et nous fournit les outils théoriques et pratiques nécessaires
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; care; corps; cours; discipline; justice reproductive; justice sociale; maternité; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques; états-unis

La Stérilisation forcée et contrainte de personnes au Canada - Canada, Sénat du (SenCanada, 2021)
Le Comité sénatorial des droits de la personne exhorte le Parlement à mener une enquête approfondie et à trouver des moyens de mettre fin à la pratique odi
Keywords: amériques; approches et analyses; canada; cours; droits des femmes*; droits des femmes* autochtones; justice reproductive; justice sociale; pol4105; premier cycle; racisme; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis